An Object-Oriented Framework for the Development of Computer-Based Guideline Implementations - Corb, G.J; Liaw, Y.; Brandt, C.A.; Shiffman, R.N. (Methods of Information in Medicine, 1999)
Clinical practice guidelines provide a means of directing medical care towards clinically appropriate and cost-effective interventions. A direct relationship exists between the integration of a guideline into clinical workflow and the effectiveness of the guideline in influencing clinicians’ behavior. Computer-based guideline implementations, used at the point-of-care, accomplish this integration. Employing object-oriented technologies, we propose a framework of reusable components for the development of guideline implementation systems. We have identified eight information management services that are common to such systems. Our framework integrates these services and their respective reusable components into clinical workflow to promote the development of comprehensive guideline implementation systems, which should ultimately enhance guideline compliance and the overall quality of care.
Keywords: Object-Oriented Framework; Clinical Practice Guidelines; Software Engineering